FOOD PACKAGING: MATERIALS, PROPERTIES, MANUFACTURING AND CHALLENGES FOR SUSTAINABILITY IN MOZAMBIQUE - Rosa, Porfírio Américo Nunes; Tanleque-Alberto, Fernando João; Minisso, Isac Claúdio; Lucas, Saidino Victor; Buma, Eni Liudmiliza Leite (Seven Editora, 2025)
Packaging is a strategic element in the food value chain, going beyond simple packaging to include protection, preservation, transportation, communication, and marketing. This chapter reviews the main packaging materials—metal, plastic, glass, cellulose, and wood—highlighting their properties, manufacturing processes, applications, and limitations. It also addresses the issue of compound migration, food safety risks, quality control methods, and the importance of recycling and sustainability in the sector. Globally, there is a drive for smart, biodegradable packaging and returnable systems aligned with the circular economy. However, in Mozambique, one of the biggest challenges remains limited access to adequate packaging, both due to dependence on imports and the lack of local processing industries. As a result, much of the post-harvest agricultural and horticultural produce is sold or stored unprotected, often exposed to the elements, which increases losses, reduces quality, and compromises food safety. The Mozambican legal framework, defined by Decree No. 15/2006, Ministerial Order No. 247/2011, and the recent Order No. 26/2025, establishes standards for labeling, safety, and sustainability. However, structural limitations persist in inspection and laboratory control, especially in migration and certification testing. Cases such as the use of returnable bottles by Cervejas de Moçambique and the ISO 22000 certification of Água da Namaacha demonstrate significant progress, but are still limited to large companies. Therefore, strengthening the packaging industry in Mozambique, combined with public incentive policies, training programs, and investment in quality laboratories, is essential to reduce post-harvest losses, add value to products, and promote the country's competitiveness in domestic and international markets.DOI: https://doi.org/10.56238/sevened2025.039-002